Changes in hematological, biochemical, and blood gases prameters in response to progressive inclusion of nitrate in the diet of Holstein calves - Ortiz Chura, Abimael; Marcoppido, Gisela Ariana; Gere, José Ignacio; Depetris, Gustavo; Stefañuk Bahamonde, Francisco José; Trangoni, Marcos David; Cravero, Silvio Lorenzo Pedro; Faverin, Claudia; Cataldi, Angel Adrian; Ceron Cucchi, Maria Esperanza (Veterinary World Publisher, 2021)
Background and Aim: Nitrate (NO3-) reduces enteric methane emissions and could be a source of non-protein nitrogen in ruminant feeds. Nonetheless, it has a potential toxic effect that could compromise animal health and production. The purpose of this study was to determine the effects of progressive inclusion of NO3- in the diet on the hematological, biochemical, and blood gases parameters, in turn, the effects on feed intake and live weight gain (LWG) in Holstein calves. Materials and Methods: Eighteen Holstein heifers and steers (nine animals/treatment) were maintained in individual pens for 45 days. Animals were randomly allocated to either a control or nitrate diet (ND) (containing 15 g of NO3-/kg of dry matter [DM]). The biochemical parameters and blood gases were analyzed only in the NO3- group on days: -1, 1, 7, 13, 19, and 25 corresponding to 0, 20, 40, 60, 80, and 100% of the total inclusion of NO3- in the diet, respectively. In addition, DM intake (DMI) and LWG were evaluated among dietary treatments. Results: Feeding the ND did not influence DMI or LWG (p>0.05). Methemoglobin (MetHb) and deoxyhemoglobin increased according to the NO3- concentrations in the diet (p<0.05), while an opposite effect was observed for oxyhemoglobin and carboxyhemoglobin (p<0.05). Hematocrit levels decreased (p<0.05), while albumin, alanine aminotransferase, and gamma-glutamyl transpeptidase concentrations were not modified (p>0.05). However, glucose, urea, aspartate aminotransferase (AST), and retinol concentrations increased (p<0.05) according to the NO3- concentrations in the diet.